2005
DOI: 10.1007/s00284-005-4531-8
|View full text |Cite
|
Sign up to set email alerts
|

Vanillate Metabolism in Corynebacterium glutamicum

Abstract: Corynebacterium glutamicum, a Gram-positive soil bacterium belonging to the mycolic acids-containing actinomycetes, is able to use the lignin degradation products ferulate, vanillate, and protocatechuate as sole carbon sources. The gene cluster responsible for vanillate catabolism was identified and characterized. The vanAB genes encoding vanillate demethylase are organized in an operon together with the vanK gene, coding for a transport system most likely responsible for protocatechuate uptake. While gene dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
98
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 23 publications
1
98
2
Order By: Relevance
“…We indeed found that NCgl1301 (PcaK) was responsible for protocatechuate and 4-hydroxybenzoate transport in C. glutamicum. However, our results were significantly different from those of Merkens et al (2005). A similar transporter was identified in P. putida (Nichols & Harwood, 1997); expression of pcaK was repressed by benzoate and preferential degradation of benzoate over 4-hydroxybenzoate was observed (Nichols & Harwood, 1995).…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…We indeed found that NCgl1301 (PcaK) was responsible for protocatechuate and 4-hydroxybenzoate transport in C. glutamicum. However, our results were significantly different from those of Merkens et al (2005). A similar transporter was identified in P. putida (Nichols & Harwood, 1997); expression of pcaK was repressed by benzoate and preferential degradation of benzoate over 4-hydroxybenzoate was observed (Nichols & Harwood, 1995).…”
Section: Discussioncontrasting
confidence: 91%
“…strain ADP1, in which VanK was reported to be also involved in 4-hydroxybenzoate and protocatechuate transport (D'Argenio et al, 1999). While working on nitrogen metabolism, Merkens et al (2005) reported that vanK mutation in C. glutamicum led to decreased growth on protocatechuate and thus proposed the occurrence of an additional protocatechuate transporter. We indeed found that NCgl1301 (PcaK) was responsible for protocatechuate and 4-hydroxybenzoate transport in C. glutamicum.…”
Section: Discussionmentioning
confidence: 99%
“…Side chain oxidation (e.g., Filley et al, 2002), demethylation, or hydroxylation (e.g., Crawford and Crawford, 1980) of compounds present in the initial DOM pool (i.e., at T0) would lead to a reduction in the abundance of those compounds at the end of the incubation and to an increase in the abundance of compounds with slightly lower molecular masses. For example, vanillic acid (∼168 Da) can be converted via demethylation to protocatechuic acid (∼154 Da) (Merkens et al, 2005). In this case, the difference in the mass of the compounds that were consumed and produced is small at 14.0157 Da (-CH 2 ).…”
Section: Discussion Temporal Changes In Dom Transformationmentioning
confidence: 99%
“…Besides, no HPr kinase/phosphatase system is found in the C. glutamicum genome. These differences in the molecular characteristics are likely reflected in the capacity of C. glutamicum to cometabolize glucose and a variety of carbon sources, including sugars, organic acids, and aromatic compounds without catabolite repression (17)(18)(19)(20)(21)(22)(23)(24), expect for a few cases (25)(26)(27).…”
mentioning
confidence: 99%